Plan de marketing para la casa deportiva LEDESMA período 2010-2011 - Peña Erazo, Carlos Jhasmany (2011)
This project was carried out on micro house Ledesma sport, it is dedicated to the manufacture and marketing of sports equipment, uniforms, physical education and sports equipment of excellent quality through timely service, effective and efficient to meet customer needs. This work responds to the need for companies to have a marketing plan that brings together all the information necessary to know the current status of the company and how it could improve the administration through a stage marketing muscle. The marketing plan for sport Ledesma house consists of chapters. CHAPTER 1 This chapter presents the introduction, the company's history, it points out the problem, formulation, justification of the research, the general objectives and specific research hypotheses are proposed for general: "The absence of Marketing Plan limits the Administrative Management of the Sports House Ledesma of the city of Quevedo. In addition, this chapter is operationalized variables hypothesis. Chapter 2 presents the literature related to the themes developed in this work. CHAPTER 3 This chapter presents the materials and the methodology of market research including calculation of sample sources to gather information required and types of surveys employed. Chapter 4 presents the results of research, summarized in tables and graphs, each with their analysis. Chapter 5 presents the main conclusions and recommendations of market research. Chapter 6 was carried out the analysis of both external and internal environment, for which use the theory of five forces M. Porter, which allowed us to know the status of the sector, opportunities and threats that this presents, while the internal analysis helped to identify the strengths and weaknesses of the company. Chapter 7 This chapter presents the expected changes proposed vision and mission of the enterprise, business values, organizational structure of the company, the classification of customers by category, marketing mix specially focusing on the following product, price , place, promotion. Also shown is the media plan, promotional plan, the respective budgets and implementation schedules.